Pelestarian Wayang “Krucil” dan Kekuatan Politik - Dian Suluh KD; Yusuf Adam Hilman (Institut Teknologi Sepuluh Nopember, 2018)
Purpose of the article is to analyze the preservation of puppets “Krucil” and the politic of powers happens in Tempuran village, Sawoo, Ponorogo. The method of the article is qualitative descriptive research and it uses in-depth interview for collecting the data. The finding of the study show that; the preservation of the puppets “Krucil” held by the government of Tempuran village annually is by having performance in “Bersih Desa”(annually societies’ activity for thanking to God after they get crop) activity. The performance of puppets “Krucil in “Bersih Desa” activity to entertain the society have been doing since the village founded. The series of events of preservation of puppets “Krucil” are Ruwat ritual conducted by every Kepala Dusun (head of hamlet), Brokohan and recitation of holy Qur’an. While, politic of powers was conducted by including “Bersih Desa” activity and performance of puppet “Krucil” to the village regulations. It was conducted by the head of village (Kepala Desa) of Tempuran based on the strong of society’s myth. The societies believe that there will be crop failure and prolonged disaster if “Bersih Desa” activity don’t performance puppets “Krucil”.